PENGARUH ILMU PENGETAHUAN DALAM PERADABAN ISLAM TERHADAP BARAT - Alfath Tri Hakiqi; Arya Abdul Alim (PT. Hasba Edukasi Mandiri, 2026)
This research discusses the influence of knowledge in Islamic civilization on the West, particularly during the Islamic Golden Age (8th to 14th centuries CE). The method used in this research is library research with a historical-factual approach and descriptive-qualitative analysis. The results show that Islamic civilization experienced rapid progress in various fields of knowledge such as mathematics, medicine, astronomy, philosophy, and technology. Figures such as Al-Khawarizmi, Ibn Sina, Al-Biruni, and Ibn Rushd produced monumental works that became world references. Islamic knowledge spread to the West through various channels, such as the translation of scientific works in Toledo, trade interactions, cultural relations, and through the Andalusian region which became an educational center. The conclusion of this research is that the influence of Islamic knowledge provided an important foundation for the development of science in the West and became one of the main factors that gave birth to the Renaissance in Europe. Thus, Islamic civilization played an important role in shaping the development of modern science as known today.